2009
DOI: 10.1172/jci37176
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function variants in endothelial lipase are a cause of elevated HDL cholesterol in humans

Abstract: Elevated plasma concentrations of HDL cholesterol (HDL-C) are associated with protection from atherosclerotic cardiovascular disease. Animal models indicate that decreased expression of endothelial lipase (LIPG)is inversely associated with HDL-C levels, and genome-wide association studies have identified LIPG variants as being associated with HDL-C levels in humans. We hypothesized that loss-of-function mutations in LIPG may result in elevated HDL-C and therefore performed deep resequencing of LIPG exons in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
149
4
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(169 citation statements)
references
References 60 publications
11
149
4
5
Order By: Relevance
“…Other than CETP, LIPC and LPL are responsible for elevated HDL-C level, and T allele of LIPC gene -514C/T polymorphism and 447X allele of LPL gene S447X polymorphism are well known to both cause 3 mg/dL of elevated HDL-C levels in Japanese (LIPC -514T allele: 75%, LPL 447X allele: 22% in Japanese population) [22,23]. If subjects who have a heterozygote of CETP mutation but rather high levels of HDL-C, further analysis involving endothelial lipase [24] and scavenger receptor class B type I (SR-BI) [25,26] activities is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Other than CETP, LIPC and LPL are responsible for elevated HDL-C level, and T allele of LIPC gene -514C/T polymorphism and 447X allele of LPL gene S447X polymorphism are well known to both cause 3 mg/dL of elevated HDL-C levels in Japanese (LIPC -514T allele: 75%, LPL 447X allele: 22% in Japanese population) [22,23]. If subjects who have a heterozygote of CETP mutation but rather high levels of HDL-C, further analysis involving endothelial lipase [24] and scavenger receptor class B type I (SR-BI) [25,26] activities is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence implies that the presence of the EL 584C/T gene polymorphism (rs2000813) is correlated to the plasma HDL-C level (Hutter et al, 2006). Edmondson et al (2009) found that the level of HDL-C increases in the loss-of-function variants of EL, and concluded that inhibition of EL may, therefore, raise the HDL-C level. In 2003, Ma et al reported that patients with the TT genotype have higher HDL-C levels than those with the CC genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that plasma EL mass measured by ELISA is inversely correlated with HDL-C concentrations in humans (15,16 ). Association-based human genetic studies have provided evidence that variations in the EL genomic LIPG locus such as T111I, G26S, and N396S are linked to differences in circulating HDL-C concentrations or CVD (17)(18)(19)(20)(21), although recent studies with a large number of subjects have established associations between LIPG single-nucleotide polymorphism and HDL-C concentrations, but none with CVD (21)(22)(23). Thus, genetic variation in EL can modulate plasma HDL-C concentrations, although the relationship with CVD remains controversial.…”
mentioning
confidence: 99%